Global stability of disease-free equilibria in a two-group SI model with feedback control - Shang, Yilun (Nonlinear Analysis: Modelling and Control, 2015)
In this letter, a two-group SI epidemic model is tackled with an eye to population mobility. Using the method of Lyapunov functions, global stability of the disease-free equilibria with respect to one group as well as both groups is investigated. We find that the disease outbreak can be effectively controlled through adjusting the feedback control variables. Examples are worked out to illustrate the theoretical results.
Keywords: global stability; epidemiological model; feedback control; population mobility